Magnetically Driven Soft Continuum Microrobot for Intravascular Operations in Microscale - Dan Liu; Xiaoming Liu; Zhuo Chen; Zhaofeng Zuo; Xiaoqing Tang; Qiang Huang; Tatsuo Arai (Cyborg and Bionic Systems, 2022)
Remotely controlled soft continuum robots with active steering capability have broad prospects in medical applications. However, conventional continuum robots have the miniaturization challenge. This paper presents a microscale soft continuum microrobot with steering and locomotion capabilities based on magnetic field actuation. The magnetically driven soft continuum microrobot is made of NdFeB particles and polydimethylsiloxane (PDMS), and it can be as small as 200 μm in diameter. Moreover, a hydrogel layer is covered on the surface of the microrobot, which not only overcomes the adhesion force between the microobjects and the soft tip but also reduces the friction between the microrobot and substrate. The performance test indicates the soft continuum microrobot featured excellent control and steering capabilities. The experimental results demonstrate that the soft continuum microrobot can travel through the microfluidic channel by its own vibration and flexibly steer in a bifurcation environment. Moreover, the micromanipulation of microbeads in the microfluidic channels proves that the proposed microscale soft continuum microrobot has a great potential for intravascular manipulation.